2014
DOI: 10.1371/journal.pone.0096992
|View full text |Cite
|
Sign up to set email alerts
|

A Face in the Crowd: A Non-Invasive and Cost Effective Photo-Identification Methodology to Understand the Fine Scale Movement of Eastern Water Dragons

Abstract: Ectothermic vertebrates face many challenges of thermoregulation. Many species rely on behavioral thermoregulation and move within their landscape to maintain homeostasis. Understanding the fine-scale nature of this regulation through tracking techniques can provide a better understanding of the relationships between such species and their dynamic environments. The use of animal tracking and telemetry technology has allowed the extensive collection of such data which has enabled us to better understand the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…In comparison, the eastern water dragon's coarse surface structure was not reported to cause reflective issues in photos or be problematic for the I 3 S software (Gardiner et al. 2014). In our study, an insufficient number of high quality reference images likely contributed to the low score in the self evaluation results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the eastern water dragon's coarse surface structure was not reported to cause reflective issues in photos or be problematic for the I 3 S software (Gardiner et al. 2014). In our study, an insufficient number of high quality reference images likely contributed to the low score in the self evaluation results.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed photo‐identification could be used to track movements of free‐ranging eastern water dragon Intellagama leseureuii and calculate their home ranges (Gardiner et al. 2014). However, few reports have investigated the broader limitations of the technique or evaluated alternative ways of using the technique for a free‐ranging reptile.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at Roma Street Parkland, there is a population in excess of 580 animals and females may overlap with up to 42 males (Gardiner et al. 2014). However, multiple matings as a consequence of frequent encounters may not be the only model that best explains water dragon mating dynamics because males control space and, as a result, females may be able to avoid particular males by closely associating with the dominant male.…”
Section: Discussionmentioning
confidence: 99%
“…Photo-ID has been widely used across taxonomic groups, such as terrestrial and marine mammals (Kelly, 2001;Langtimm et al, 2004), reptiles (Schofield et al, 2008;Gardiner et al, 2014) and fish (Couturier et al, 2014;Kanive et al, 2015). Photo-ID is considered a largely non-invasive method by which animals are initially "captured" in photographs, and subsequently matched through photographic "recaptures" to create an individual's capture history.…”
Section: Introductionmentioning
confidence: 99%